164: The Health Burden of Invasive Meningococcal Disease: A Systematic Review. Issue 6 (1st June 2014) - Strifler, L; Morris, SK; Dang, V; Tu, HT; Minhas, R; Jamieson, FB; Deeks, SL; Crowcroft, N; Sander, B
Abstract: BACKGROUND: Although rare, invasive meningococcal disease (IMD) continues to be a health concern in high-income countries, as it results in severe morbidity and relatively high case fatality, especially in young children. However, studies measuring sequelae of IMD across the spectrum of invasive syndromes have not been systematically reviewed. OBJECTIVES: To conduct a systematic review on sequelae attributable to IMD as well as quality of life in survivors in high-income countries. DESIGN/METHODS: We searched MEDLINE, EMBASE and HealthStar up to April 2013 and scanned the reference lists of relevant systematic reviews and included studies. Primary studies assessing sequelae and/or quality of life in individuals with IMD and a comparator group were eligible for inclusion. Two reviewers independently screened articles (titles and abstracts, followed by full text), abstracted data and performed quality appraisal. Findings were summarized qualitatively. RESULTS: Of 1884 citations screened, 22 articles reporting on 17 studies were included. The most commonly assessed sequelae were hearing impairment (in five studies), cognitive impairment (seven studies), and psychological problems (six studies). Compared with controls, IMD survivors had greater incidence of hearing loss (in children), lower mean IQ test score (children), greater incidence of psychological disorders (eg, ADHD [children], depression [adolescents/adults]), and lower overall quality of life. There were no significant differences in overall cognitive function between exposed and unexposed adults. Odds of death were significantly increased with IMD at hospital discharge and up to 30 years after disease; however, the role of pre-existing co-morbidities remains unclear. CONCLUSIONS: A better understanding of the breadth of IMD sequelae in high-income countries is critical to support healthcare planning and decision-making. In particular, this information is useful to assess of the burden of IMD in light of new vaccines.